Good act, poor implementation: the report of the House of Lords Post-Legislative Scrutiny Committee on the Mental Capacity Act 2005 - Bartlett, Peter (Jordan, 2014)
The House of Lords Post-Legislative Scrutiny Committee on the Mental Capacity Act 2005 reported on 13 March 2014. This paper considers the findings and recommendations of the Committee, and in particular its two key recommendations – the establishment of an independent oversight body to co-ordinate implementation of the Act, and the need to develop a replacement for the present deprivation of liberty safeguards (DOLS).